PENGARUH PEMBINAAN, PEMANTAUAN DAN INSENTIF TERHADAP MOTIVASI KERJA PENGELOLA LEMBAGA PAUD NON FORMAL - Santoso, Srijono Pudji; Widajanti, Erni - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT The purpose of this research are: 1) Analyze the influence of supervising on motivation of work 2) Analyze the influence of monitoring on motivation of work 3) Analyze the influence of incentives on motivation of work 4) Analyze variables supervising, monitoring and incentives that the dominant influence work motivation. This research is explanatory. Locations throughout the Paud Non Formal Institutes Kebakkramat Sub District In The Coordination of UPT. PUD, NFI and SD Office Kebakkramat District. This study population is the all of education personnels and educators on Kebakkramat District in the UPT, PUD, NFI and SD office Kebakkramat District by 40 respondents to the census sampling techniques. Types of data using quantitative and qualitative data. Source of data using primary data and secondary data. The technique of collecting data using interviews and questionnaires. Analysis techniques using test validity, test reliability test classic assumptions, multiple linear regression, t test, F test, the coefficient of determination. Keywords: coaching, monitoring, incentives, work motivation.